Assessment of 16S rRNA Gene-Based Phylogenetic Diversity of Archaeal Communities in Halite-Crystal Salts Processed from Natural Saharan Saline Systems of Southern Tunisia - Afef Najjari; Panagiota Stathopoulou; Khaled Elmnasri; Faten Hasnaoui; Ines Zidi; Haitham Sghaier; Hadda Imene Ouzari; Ameur Cherif; George Tsiamis (Biology, 2021)
A thorough assessment of the phylogenetic diversity and community structure of halophilic archaea from three halite-crystal salts, processed from two separated saline systems of Southern Tunisia has been performed using culture dependent and independent methods targeting different regions of 16S rRNA gene sequences including DGGE, 16S rRNA clone libraries and Illumina Miseq sequencing. Two samples, CDR (red halite-crystal salts) and CDW (white halite-crystal salts), were collected from Chott-Eljerid and one sample CDZ (white halite-crystal salts) from Chott Douz. Fourteen isolates were identified as Halorubrum, Haloferax, Haloarcula, and Halogeometricum genera members. Culture-independent approach revealed a high diversity of archaeal members present in all samples, represented by the Euryarchaeal phylum and the dominance of the Halobacteria class. Nanohaloarchaea were also identified only in white halite samples based on metagenomic analysis. In fact, a total of 61 genera were identified with members of the Halorhabdus, Halonotius, Halorubrum, Haloarcula, and unclassified. Halobacteriaceae were shared among all samples. Unexpected diversity profiles between samples was observed where the red halite crust sample was considered as the most diverse one. The highest diversity was observed with Miseq approach, nevertheless, some genera were detected only with 16S rRNA clone libraries and cultured approaches.